Looking Back, Looking Forward: Feminist Legal Scholarship in SLS. (December 2017) - Boyd, Susan B; Parkes, Debra
This article offers a review of shifts in feminist legal theory since the early 1990s. We first use our respective histories and fields of expertise to provide a brief overview and highlight some key themes within feminist legal theory. We then examine Social & Legal Studies ( SLS ), asking whether it has met its key goal of integrating feminist analyses at every level. Our review suggests that SLS has offered many important contributions to feminist legal scholarship but has not fulfilled its lofty goal of integrating feminist analyses at every level of scholarship. It features feminist work quite consistently and some degree of mainstreaming is evident, as is the international reach of SLS. Too many articles fail, however, to incorporate or even mention feminist approaches. We end with thoughts about, and hopes for, the future of legal feminism, examining efforts to revitalize the field and suggesting possible directions for the future.